A framework for integrating sustainable development concepts into the chemistry curriculum towards achieving education for sustainable development in Malaysia - Kanapathy, S. (Emerald Group Holdings Ltd., 2021)
Purpose: In Malaysia, research indicates that there is an interest amongst the stakeholders, namely, administrators and academicians to be engaged in education for sustainable development (SD), but it is rarely implemented as a part of the higher education curriculum due to various barriers. This paper aims to develop a framework for integrating SD concepts into the chemistry curriculum, using a case study approach. Design/methodology/approach: This study was conducted at a local university located in Selangor, Malaysia, offering a foundation programme to students between 17 to 18 years of age. Data was collected using a qualitative approach that involved 12 experts as informants. The collected data was analysed via three coding stages, namely, open coding, category coding and thematic encoding using Atlas.ti 7.0 software. Findings: The research revealed that six aspects contribute to the integration of SD concepts into the chemistry curriculum, namely, educational policy, awareness, resources, curriculum, pedagogical approach and stakeholdersâ engagement. The proposed framework was formulated by considering these aspects. Originality/value: The findings of this study can be used as a guide to facilitate the integration of SD concepts into the chemistry curriculum. It is expected to encourage the involvement of more teachers in adopting sustainable chemistry teaching. Â© 2021, Emerald Publishing Limited.